Adaptation and validation into Spanish of the Multidimensional Psychological Flexibility Inventory (MPFI): evidence of internal validity and factorial Invariance - Simkin, Hugo Andrés (2023)
This study aims to assess the psychometric properties and internal consistency of the Spanish version of the Multidimensional Psychological Flexibility Inventory (MPFI) within a general population of Argentina. A total of 866 participants with ages between 18 and 84 years (M = 47.33; SD = 17.26) and of both sexes (Men = 40.9%; Women = 59.1%) participated in the main study. A 2-factor higher order model resulted in acceptable fit indices (NFI = .97; NNFI = .98; CFI = .98; IFI = .98; RMSEA .41). The Spanish MPFI also demonstrated both weak (metric) and strong (scalar) factor invariance when compared to the English MPFI given to a United States sample (N = 1630; 18 to 85 years old, M = 50.1, SD = 18.7; 77.0% identifying as women; 86.6% White). Results indicated an acceptable internal consistency in all factors (ω >.74). The adaptation into Spanish of the MPFI presents 60 and 24 items similar to those proposed by the original authors and adequate psychometric properties in the study sample. Regarding its limitations, it should be noted that results only report the factor structure -factor validity- and the internal consistency -reliability- of the MPFI, which is only a first exploratory approach in adapting the scale to the local context. For this reason, future research should continue to explore the psychometric properties of the MPFI in Argentina.